SIKAP, POLA PEMBELIAN DAGING SAPI DAN FAKTOR-FAKTOR YANG MEMENGARUHI RUMAH TANGGA DI PASAR RAYA LEBAK BUDI KOTA BANDAR LAMPUNG - Jenny Rosianna Situmeang; Yaktiworo Indriani; Maya Riantini (Lampung University, 2026)
This study aimed to examine the attitudes of household consumers, beef purchasing patterns, and factors that influenced beef purchased by the consumers. This study was conducted using a survey method at Pasar Raya Lebak Budi, Bandar Lampung City, with simple random sampling method to select the respondent.. The respondents consisted of 33 housewives. The data were collected in December 2024, and analyzed using Fishbein Multi-Attribute analysis, descriptive analysis, and multiple linear regression analysis. The results showed that the respondents were housewives aged 25-50 years old with educational backgrounds ranging from junior high school to university, had 3-7 family members, and household incomes ranging from IDR 4,000,000.00 to IDR 7,000,000.00 per month. The pattern of beef purchasing among housewives involved the purchase of main cuts of beef. The amount of beef purchased in the last month was 1–2 kg per month, with a purchase frequency was twice per month. The consumer attituded score towards beef attributed based on the Fishbein Multi-Attribute Model was 151.19, which fell into the “like” interpretation range of 123.20–161.50. The factors that influenced beef purchased by households were the price of beef and the price of chicken eggs. Keywords: attitudes, beef, household, purchasing patterns